1992
DOI: 10.21273/hortsci.27.12.1297
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Flooding Affects Gas Exchange Characteristics of Containerized Sour Cherry Trees

Abstract: The effects of short-term soil flooding on gas exchange characteristics of containerized sour cherry trees (Prunus cerasus L. cv. Montmorency /P. mahaleb L.) were studied under laboratory conditions. Soil flooding reduced net CO2 assimilation (A) within 24 hours. Net CO2 assimilation and residual conductance to CO2(gr′) declined to ≈30% of control values after 5 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 16 publications
(17 reference statements)
4
19
0
1
Order By: Relevance
“…However, a plausible explanation can be offered that P n drastically reduced in flooded plants up to 3-days because of both stomatal and non-stomatal limitations, and thereafter, plants could acclimatize to flooding situation and non-stomatal limitation became dominant. This is also in agreement with the report by Beckman et al (1992) and Kozlowski and Pallardy (1984) that photosynthesis of flooded plants appears to be reduced first primarily because of stomatal closure and later by a reduction in photosynthetic capacity. Genotypic differences in recovery of P n were highly evident at vegetative and flowering stages.…”
Section: Discussionsupporting
confidence: 93%
“…However, a plausible explanation can be offered that P n drastically reduced in flooded plants up to 3-days because of both stomatal and non-stomatal limitations, and thereafter, plants could acclimatize to flooding situation and non-stomatal limitation became dominant. This is also in agreement with the report by Beckman et al (1992) and Kozlowski and Pallardy (1984) that photosynthesis of flooded plants appears to be reduced first primarily because of stomatal closure and later by a reduction in photosynthetic capacity. Genotypic differences in recovery of P n were highly evident at vegetative and flowering stages.…”
Section: Discussionsupporting
confidence: 93%
“…Stomatal closure hinders CO 2 absorption, on the other hand, hypoxia induced by waterlogging inhibits synthesis of 8-amino-propyl acetate (5-ALA), the speed limit step of chlorophyll synthesis. Reduced CO 2 -fixation ability of chloroplast and chemical changes of PSII system will lead to significant decrease in leaf photosynthetic rate (Beckman et al 1992, Olien 1989. Our results showed that the photosynthetic rate and stomatal conductance of the five pepper species and wild pepper dramatically decreased under waterlogging condition and their recovery to normal levels after the drainage is lagged behind and needs time, indicating that pepper is not a good waterlogging-tolerant plant.…”
Section: Discussionmentioning
confidence: 99%
“…5), suggests that carbon assimilation was only affected by stomatal closure. Similarly in Prunus cerasus, much of the early decrease in photosynthesis of flooded plants was attributed to stomatal inhibition (Beckman et al 1992).…”
Section: Discussionmentioning
confidence: 99%